Training hip flexors as a joint stabiliser for injury prevention. - Barnitt, G. J. (Journal of Australian Strength and Conditioning, 2017)
The research literature suggests that the hip flexors have an important role in stability of the hip joint. Evidence of this and the role of hip flexors in injury prevention is outlined. The second part of this article looks at how to include hip flexor exercises into a resistance training program. Details of how to perform specific exercises and how they maybe progressed are provided.